Microstructure turbulence, conductivity-temperature-depth, and current velocity measurements of a submesoscale eddy in Terra Nova Bay (2018-2019) - Friedrichs, Andrew; McInerney, Jasmin; Oldroyd, Holly; Lee, Won Sang; Yun, Sukyoung; Yoon, Seung-Tae; Stevens, Craig; Zappa, Christopher; Dow, Christine; Mueller, Derek; Sepulveda Steiner, Oscar; Forrest, Alex (Zenodo, 2023)
Antarctica's ice shelves buttress the continent's terrestrial ice, helping slow the loss of grounded ice into the ocean and limiting sea level rise. Ice-ocean interaction plays a critical role ice shelf stability by driving basal melt rates. Consequently, improved prediction of the future state of ice shelves lies in understanding the coastal ocean mechanics that deliver heat to their cavities. Here, we present autonomous glider-based observations of a coherent structure at the calving front of a cold-water cavity ice shelf (Nansen Ice Shelf, East Antarctica). This ~10 km-wide eddy dominated the local ocean circulation, promoting an upwelling of cold ice shelf water and a deepening of warm surface water. Microstructure turbulence measurements show resulting vertical heat transport of ????(10 W m-2) at depths equivalent to the ice shelf draft. Similar eddy-driven heat transport further into the ice shelf cavity would support enhanced summertime melt in regions of shallower ice draft. All of these data are .csv files and are able to be opened in Microsoft Excel or equivalent. Funding provided by: Antarctic Science Platform* Crossref Funder Registry ID: Award Number: ANTA1801 Funding provided by: Korean Ministry of Oceans and Fisheries* Crossref Funder Registry ID: Award Number: KIMST20190361 Funding provided by: Korean Ministry of Oceans and Fisheries* Crossref Funder Registry ID: Award Number: PM21020